The implementation of credit relaxation through credits restructuring for debtors in terms of credit payments delaying obligations in the era of pandemic 19 in Indonesia (Research, Society and Development, 2020)
Applying business capital for a loan from a bank is a common thing to do for every aspiring businessman. In making the loan, the businessman uses a period and pays the monthly installments in accordance to what has been agreed. At the end of 2019, the outbreak of the Corona Pandemic 19 virus in the world has begun and without exception in Indonesia, resulting in decreased income from business sector. In order to address this problem as well as to ease bank installments for business people, Credit Restructuring can be carried out. This research is a normative juridical research, namely legal research by employing secondary data as a basic material by conducting an examination of the regulations and literature related to Credit Restructuring. As a result, it can be argued that the implementation of restructuring for each debtor is unquestionably different depending on the credit risk by the debtor and depends on the policy and analysis of the bank itself. Not all parties can accept this credit relaxation where banks or multi-finance companies are still required to be watchful for it is full of risk management calculations, thus relaxation is only given to debtors who have a good track record and are certainly affected by economic pressure due to the corona virus Pandemic 19. Credit Relation is running in accordance with the provisions of Government Regulation in Lieu of Law (Perppu) Number 1 of 2020 which is followed up by the Financial Services Authority (OJK) through policies, one of which regulates the Credit Relaxation Policy through Credit Restructuring for Debtors affected by Covid 19 especially for Small Micro Medium Enterprises.